Performance of Bio-slurry and Inorganic Fertilizer on Growth, Yield and Quality of Indian Spinach (Basella alba L.) - Mst. Morium Akter (Journal of the Bangladesh Agricultural University, 2021)
An experiment was conducted at the Horticulture Farm of Bangladesh Agricultural University, Mymensingh during the period from March to June 2018 to investigate the effects of organic fertilizer like bio-slurry and inorganic fertilizer on the growth and yield of Indian spinach (Basella alba L.). The experiment consisted of six treatments following a randomized complete block design with three replications. The treatments were T1- Inorganic fertilizer (100%), T2-Inorganic fertilizer (75%) and bio-slurry (25%), T3- Inorganic fertilizer (50%) and bio-slurry (50%), T4- Inorganic fertilizer (25%) and bio-slurry (75%), T5- Organic fertilizer (100%), and T6- No organic or inorganic fertilizers (control). Here, bio-slurry was used as a source of organic fertilizer. The highest vine length (31.13cm), leaf numbers/plant (40.80 cm), leaf length (15.67cm), leaf breadth (9.13 cm), number of branch per plant (7.00), vine diameter (0.71 cm), yield per plot (16.20 kg) and per ha (30.92 ton), dry matter of leaf (11.27%), dry matter of vine (6.11%) were obtained from T4 (inorganic fertilizer: 25% and organic fertilizer: 75%) treatment. The lowest value of vine length (18.33 cm), leaf numbers per plant (22.07cm), leaf length (11.61cm), leaf breadth (6.78cm), number of branch per plant (2.33), vine diameter (0.47cm), yield per plot (4.08kg) and per ha (8.03 ton), dry matter of leaf (9.86%), dry matter of vine (5.5%) was obtained from T6 (control) treatment. The vine length was found 40% and 41% higher at 30 and 45 days after sowing, respectively under T4 treatment compared to control. Overall, the yield and other parameters were found significantly different and the highest yield from T4 was found significantly 212% higher compared to control. Therefore, the combined application of bio-slurry and inorganic fertilizer can promote the sustainable and eco-friendly production of Indian spinach. [J Bangladesh Agril Univ 2021; 19(3.000): 287-293]